Asymmetric boron conjugate addition to α, β-unsaturated carbonyl compounds catalyzed by CuOTf/Josiphos under non-alkaline conditions. Issue 1 (8th December 2014) - Xie, Jian-Bo; Lin, Siqi; Luo, Jian; Wu, Jianbin; Winn, Timothy R.; Li, Guigen
Abstract : The asymmetric boron conjugate addition onto α, β-unsaturated ketones and esters has been developed by using the CuOTf/Josiphos complex as the catalyst under non-alkaline conditions. Abstract : The asymmetric boron conjugate addition onto α, β-unsaturated ketones and esters has been developed by using the CuOTf/Josiphos complex as the catalyst under non-alkaline conditions. It was found that the addition of MeOH into the reaction system is crucial to the catalytic reactivity. Good to excellent enantioselectivity (up to 96% ee) and yields (up to 98%) have been achieved for 15 examples.